2018
DOI: 10.1016/j.artd.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Intrawound vancomycin in primary hip and knee arthroplasty: a safe and cost-effective means to decrease early periprosthetic joint infection

Abstract: BackgroundPeriprosthetic joint infection (PJI) is a devastating complication after hip and knee arthroplasty. Intrawound vancomycin has been described extensively in the spine literature; however, information regarding use in arthroplasty is limited. We investigate the efficacy and safety of intrawound vancomycin in arthroplasty surgery.MethodsAll primary total hip and knee arthroplasty cases (n = 460) performed by a single surgeon from April 2016 to October 2017 were reviewed. Starting in October 2016, intraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 30 publications
0
63
1
Order By: Relevance
“…In a subgroup analysis, the effect in revision operations was even greater, with a reduction of the infection rate from 3.9 to 0%. Patel et al showed a reduction in the infection rate through vancomycin of 2.7–0.3% and determined a number needed to treat (NNT) of 47.5 12 . Systemic side effects were not observed.…”
Section: Introductionmentioning
confidence: 99%
“…In a subgroup analysis, the effect in revision operations was even greater, with a reduction of the infection rate from 3.9 to 0%. Patel et al showed a reduction in the infection rate through vancomycin of 2.7–0.3% and determined a number needed to treat (NNT) of 47.5 12 . Systemic side effects were not observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although clinical observational studies have shown significant efficacy using intrawound vancomycin powder in spine surgery, a meta‐analysis indicated that prospective randomized data do not support this conclusion 56 . In the arthroplasty literature, while several retrospective observational studies have reported significantly decreased infection and reoperation rates in wounds that have been treated with vancomycin powder, 57 others have found significantly increased aseptic wound complications attributed to the vancomycin powder, possibly related to local adverse response 58 . Currently, there is no high‐level evidence to direct the use of intrawound vancomycin powder.…”
Section: Resultsmentioning
confidence: 99%
“…The literature on the efficacy of VP in arthroplasty remains inconclusive. Although some studies have shown a decrease in overall infection rates, incidence of periprosthetic joint infection and readmission rates for infection [14], others have shown no difference in reoperation rates or infection rates [15].…”
Section: Discussionmentioning
confidence: 99%
“…Complications experienced by patients. Many surgeons continue to use VP, as most studies have determined no increased risk to the patient (ie, ototoxicity, nephrotoxicity) [14] or to implant longevity [16]. In prior studies examining soft tissue concentrations of vancomycin, IO vancomycin has reached levels of 44 mg/g in fat and 38 mg/g in bone [3], whereas intrawound VP has demonstrated 207 mg/mL concentrations within the drainage fluid at 24 hours [17].…”
Section: Tablementioning
confidence: 99%